A Prática reflexiva no ensino de língua estrangeira: reflexões docentes - FERREIRA, Synndy Emilly dos Santos (2023)
This article aims at approaching aspects of the reflective practice of teaching action - reflective teaching – and It proposes analyzes of the possible changes that this practice can cause in the teaching action in the context of teaching-learning of a foreign language. The motivation for this research originates from the extension project ABC English: opening doors, in which teacher training is a priority aspect and the practice of reflection stands out as a tool to promote the improvement of teaching quality. The study is developed through bibliographic research and It uses as support theoretical references Nóvoa (1992), Schön (1992, 2000), Soisangwarn and Wongwanich (2014), Zeichner (2008), among others. It is hoped that the results of this work may contribute to other research in this area and to the training of undergraduate students by promoting the importance of self-criticism and self-reformulation based on reflective logic.